MELESTARIKAN BUDAYA TULIS NUSANTARA: Kajian tentang Aksara Lontara - Abdul Aziz Ahmad (Jurnal Budaya Nusantara, 2014)
The conservation of Indonesian Traditional Script is less seriously done. Therefore it needs to be encouraged especially for the traditional scripts because they are one of the national assets which need to be developed and kept. Lontara, traditional script in Indonesia, is the one which is still exist in use in South Sulawesi, although it is restricted in small areas. The term Lontara means history and science, and the second meaning is something written, or an article. Lontara script is also well known as Bugis Script or Makassar Script, but people prefer saying it as Lontara Script. The effort to introduce the Lontara is done in the following ways firstly by introducing the use and the benefit of the script. People are usually not interested to something because they do not know it. Secondly, it is done by reading and writing. Thirdly is by promoting the people to use it in daily written communication. Fourth is by using it in a publication, or written media, because this script needs to be spread out through a latest modern technology. Fifth is showing the Lontara to the people in a form of Artistic Craft, or paintings. Keywords: script, lontara, traditional, communication, publication.